2015
DOI: 10.7287/peerj.preprints.1430
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variation in the flowering time orthologs BrFLC and BrSOC1 in a natural population of Brassica rapa

Abstract: Understanding the genetic basis of natural phenotypic variation is of great importance, particularly since selection can act on this variation to cause evolution. We examined expression and allelic variation in candidate flowering time loci in Brassica rapa plants derived from a natural population and showing a broad range in the timing of first flowering. The loci of interest were orthologs of the Arabidopsis genes FLC and SOC1 (BrFLC and BrSOC1, respectively), which in Arabidopsis play a central role in the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…We propose that early expression of genes repressed by FLC paralogs, such as SOC1 and SPL15, might contribute to early owering in these F 3 lines due to the br c-y allele. Franks et al (2015) reported that the total amount of SOC1 expressed is strongly correlated with owering time. If a SOC1 allele circumventing FLC repression is identi ed, early-owering can be accelerated further by combining this with BrFT2-C.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that early expression of genes repressed by FLC paralogs, such as SOC1 and SPL15, might contribute to early owering in these F 3 lines due to the br c-y allele. Franks et al (2015) reported that the total amount of SOC1 expressed is strongly correlated with owering time. If a SOC1 allele circumventing FLC repression is identi ed, early-owering can be accelerated further by combining this with BrFT2-C.…”
Section: Discussionmentioning
confidence: 99%
“…Plant flowering is a coherent and complex process, and flowering-related genes such as SEP , APETALA , AG , and AGL comprehensively regulate flower formation [ 47 ]. Numerous studies have shown that FLC can block the transcriptional activation of SOC1 and requires SVP expression to delay flowering [ 48 ]. In the present study, the fluorescence quantitative results showed that the expression levels of PdMADS47 ( SVP ) and PdMADS16 ( AGL12 ) were significantly increased in the dormant stage of ‘Nonpareil’ almond flower buds, while PdMADS35 ( FLC ) and PdMADS23 ( SOC1 ) were expressed at a normal level in B1.…”
Section: Discussionmentioning
confidence: 99%
“…PdMADS family member protein interaction analysis can predict the functions of these genes [ 42 ]. SOC1 is an important gene for regulating flowering, and its overexpression can suppress late flowering in plants with functional FRI and FLC alleles [ 48 ]. Notably, this study found that SOC1 ( PdMADS23 , 26 , and 39 ) interacts with multiple groups of genes, such as SEP ( PdMADS42 ), APETALA3 ( PdMADS61 ), and AGAMOUS ( PdMADS36 ).…”
Section: Discussionmentioning
confidence: 99%
“…B. rapa has been sequenced and annotated (Zhang et al, 2018). B. rapa is closely related to A. thaliana (Cheng et al, 2014; Franks et al, 2015; Wang et al, 2011), but is self‐incompatible and reproduces only by outcrossing. The B. rapa population we used in this study originated from the San Joaquin Marsh Reserve in Orange County, CA in 1997 (Franks et al, 2007), and seeds were collected after several years of greater than average precipitation.…”
Section: Methodsmentioning
confidence: 99%